Addressing Vata Vyadhi With Ayurveda: A Case Study (Prakriti - The International Multidisciplinary Research Journal, 2025)
Vata Vyadhi encompasses a broad range of neuromuscular, musculoskeletal, and  degenerative disorders caused by Vata Dosha vitiation, leading to symptoms such  as pain, stiffness, and mobility impairment. This case study evaluates the impact of  Ayurvedic interventions in managing Vata Vyadhi in a 60-year-old female patient  who visited Jeena Sikho Lifecare Limited Hospital, Mathura, Uttar Pradesh, India.  She presented with radiating lower limb pain, knee joint pain, and left-sided  radiculopathy. The patient underwent Ayurvedic treatment, including dietary  modifications, Ayurvedic formulations, and lifestyle management. Post-treatment,  she experienced significant pain relief and improved mobility, with no recurrence of  symptoms. Additionally, improved vital signs and laboratory parameters indicated  a positive therapeutic response. From a modern perspective, VataVyadhi correlates  with conditions like osteoarthritis, sciatica, and neuropathy, often diagnosed  through MRI, CT scans, and inflammatory markers. While conventional medicine  relies on analgesics, muscle relaxants, and surgery, Ayurvedic treatment offer a  holistic approach addressing both symptoms and underlying pathology. This  case highlights the potential efficacy of Ayurveda in Vata disorder management,  though further clinical trials and standardized protocols are needed to validate  these findings and integrate Ayurveda into mainstream healthcare.
Keywords: Vata Vyadhi; Ayurveda; Vata Dosha; Sandhigata Vata; Knee joint pain; Type 2 diabetes mellitus; Madhumeh